Parasite specialization in a unique habitat: hummingbirds as reservoirs of generalist blood parasites of Andean birds - Moens, Michael (2016)
Understanding how parasites fill their ecological niches requires information on the processes involved in the colonization and exploitation of unique host species. Switching to hosts with atypical attributes may favour generalists broadening their niches or may promote specialization and parasite diversification as the consequence. We analysed which blood parasites have successfully colonized hummingbirds, and how they have evolved to exploit such a unique habitat. We specifically asked (i) whether the assemblage of Haemoproteus parasites of hummingbirds is the result of single or multiple colonization events, (ii) to what extent these parasites are specialized in hummingbirds or shared with other birds and (iii) how hummingbirds contribute to sustain the populations of these parasites, in terms of both prevalence and infection intensity. We sampled 169 hummingbirds of 19 species along an elevation gradient in Southern Ecuador to analyse the host specificity, diversity and infection intensity of Haemoproteus by molecular and microscopy techniques. In addition, 736 birds of 112 species were analysed to explore whether hummingbird parasites are shared with other birds. Hummingbirds hosted a phylogenetically diverse assemblage of generalist Haemoproteus lineages shared with other host orders. Among these parasites, Haemoproteus witti stood out as the most generalized. Interestingly, we found that infection intensities of this parasite were extremely low in passerines (with no detectable gametocytes), but very high in hummingbirds, with many gametocytes seen. Moreover, infection intensities of H. witti were positively correlated with the prevalence across host species. Our results show that hummingbirds have been colonized by generalist Haemoproteus lineages on multiple occasions. However, one of these generalist parasites (H. witti) seems to be highly dependent on hummingbirds, which arise as the most relevant reservoirs in terms of both prevalence and gametocytaemia. From this perspective, this generalist parasite may be viewed as a hummingbird specialist. This challenges the current paradigm of how to measure host specialization in these parasites, which has important implications to understand disease ecology. © 2016 The Authors. Journal of Animal Ecology © 2016 British Ecological Society.